Borrower's moral hazard, risk premium, and welfare: a comparison of universal and stand-alone banking systems - Banerji, Sanjay; Basu, Parantap (Elsevier, 2015)
Does the unification of retail and investment banking necessarily heighten risk in financial markets? Using a simple two period intertemporal model with borrower's moral hazard and uninsured risk, we argue that the integration in financial service markets under universal banking could give rise to a greater risk sharing arrangement. This could eliminate the stock market premium attributed to borrower's moral hazard. Absent any other frictions, we show that there is an unambiguous output and welfare gain from switching to a universal banking system from retail banking because of this efficient risk sharing. This welfare gain is higher in economies prone to greater information friction caused by borrower's moral hazard.